2004
DOI: 10.1261/rna.7186504
|View full text |Cite
|
Sign up to set email alerts
|

Modified nucleotides at the 5′ end of human U2 snRNA are required for spliceosomal E-complex formation

Abstract: U2 snRNA, a key player in nuclear pre-mRNA splicing, contains a 5-terminal m 3 G cap and many internal modifications. The latter were shown in vertebrates to be generally required for U2 function in splicing, but precisely which residues are essential and their role in snRNP and/or spliceosome assembly is presently not clear. Here, we investigated the roles of individual modified nucleotides of HeLa U2 snRNA in pre-mRNA splicing, using a two-step in vitro reconstitution/complementation assay. We show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 41 publications
(46 reference statements)
1
128
1
2
Order By: Relevance
“…Later work carried out by the Luhrmann group looked into the role that pseudouridines of mammalian U2 snRNA play in pre-mRNA splicing in Hela cell extracts (Donmez et al, 2004). Their results confirmed that pseudouridines are required for the formation of early spliceosomal complexes; U2 lacking pseudouridine residues was found incompetent at forming complexes A, B1, B2, and C (Fig.…”
Section: Pseudouridylation Of U2 Is Required For Snrnp Assemblymentioning
confidence: 78%
“…Later work carried out by the Luhrmann group looked into the role that pseudouridines of mammalian U2 snRNA play in pre-mRNA splicing in Hela cell extracts (Donmez et al, 2004). Their results confirmed that pseudouridines are required for the formation of early spliceosomal complexes; U2 lacking pseudouridine residues was found incompetent at forming complexes A, B1, B2, and C (Fig.…”
Section: Pseudouridylation Of U2 Is Required For Snrnp Assemblymentioning
confidence: 78%
“…When modeled with RNA oligomers, the presence of ⌿ in U2 small nuclear RNA causes a change in the structure of the lariat branch point of pre-messenger RNA (35,36). A functional requirement for ⌿ in U2 small nuclear RNA has also been shown in reconstitution of splicing systems (37)(38)(39). The loss of ⌿ in tRNAs may alter the structure of the tRNA and have an impact on its role in the translation process.…”
Section: Discussionmentioning
confidence: 99%
“…All snRNAs are capped at their 5′ ends by TMG, and internal bases are modified by scaRNAs present in the CB 7 . Internally modified nucleotides are required for U2 snRNP function, whereas the TMG cap is not 38 . Therefore, we tested modified U1 and U2 snRNAs purified from mature human snRNPs in our assay ( Supplementary Fig.…”
Section: Mature Human Spliceosomal Snrnps Rescue the Coilin Morphantmentioning
confidence: 99%